Sociomuseologia, Museologia Social e a Sociologia dos Museus (Cadernos de Sociomuseologia, 2025)
This paper seeks to clarify the distinctions between Sociomuseology, Social Museology and the Sociology of Museums. While these concepts are interconnected, they hold distinct meanings in both theory and practice. By engaging with these themes, this paper contributes to an ongoing debate on the conceptual boundaries and intersections of Sociomuseology, Social Museology, and the Sociology of Museums, urging a more nuanced understanding of their respective roles in contemporary museology.This article also engages with certain core ideas, at times reinforcing key arguments and at other times offering complementary perspectives that call for greater conceptual flexibility. It highlights three primary questions, which are relevant beyond the Chinese context: a) Museology as a subject of sociological approach; b) The position of Social Museology and Sociomuseology within contemporary museology; c) Issues of professionalization and specialization in museologyKeywords: Sociomuseology; Social Museology; Sociology of Museums